Individual adaptability to changes at work new directions in research - Chan, David (Organization and management series (Routledge (Firm)), 2014)
"In the past two decades there has been increasing interest in the research on individual adapta-bility, and this is one of the first academic volumes to look at this important topic. Specific con-texts examined include work-family conflict, retirement, career management and intercultural interaction at the workplace. The book will provide a comprehensive and integrated analysis of the conceptual, assessment and contextual issues that will help identify the current trends and emerging themes in adaptability research. "-- |c Provided by publisher.